Tinjauan Perda Pengendalian Kebakaran Lahan: Studi Kasus di Jalan Pamajatan, Gambut - Dhianingtyas, Zena Lulu (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2025)
This study aims to analyze the Regional Regulation of Banjar Regency Number 6 of 2013 concerning the Control of Environmental Damage Caused by Forest and/or Land Burning, focusing on the conflict between the interests of local farmers and the prevailing environmental law provisions. Normatively, this regulation was established to prevent environmental degradation caused by land burning activities, particularly in peatland areas. In practice, however, farmers in Gambut District continue to burn land as a traditional method of cultivation and pest control for local paddy (banih habang), due to the absence of effective non-burning agricultural technologies provided by the government. This research employs a normative juridical method with a statutory and conceptual approach, using literature study techniques through analysis of laws, legal doctrines, and related documents. The results indicate that normatively, this regulation aligns with the environmental law principles stipulated in Law Number 32 of 2009 on Environmental Protection and Management, namely the principles of state responsibility, precaution, sustainability, and participation. However, substantively, its implementation has not been effective, as it has not been responsive to the socio-economic conditions of the farming community. The study concludes that the effectiveness of Regional Regulation No. 6 of 2013 depends not only on its normative content and sanctions, but also on the government’s ability to provide fair and practical alternatives for farmers, such as non-burning technology, environmental law education, and participatory policies that promote community legal awareness.